Radiation Embrittlement Understanding for PLIM Activities at EC-JRC-IE - Debarberis, L.; Sevini, F.; Acosta, B.; Pirfo, S.; Bieth, M.; Weisshaeupl, H.; Törrönen, K.; Kryukov, A.; Valo, M. (Проблемы прочности, 2004)
Radiation embrittlement and aging mechanisms
for NPP reactor pressure vessels and vessel internals
have been studied within NPP Plant Life Management
(PLIM) for evaluation, prediction, and
monitoring of the critical components’ service life.
The main achievements of the SAFELIFE project,
integrating various networks on PLIM issues, are
given. Results of neutron embrittlement of model
alloys are presented, and surveillance and research
data on WWER reactor pressure vessel and other
steels have been analyzed. Projects for the development
of destructive and non-destructive testing of
irradiated materials have been outlined. В рамках программы PLIM исследовано радиационное охрупчивание и механизмы старения
конструкционных сталей внутрикорпусных устройств реакторов с целью оценки, прогнозирования
и мониторинга ресурса ответственных узлов АЭС. Изложены результаты проекта
SAFELIFE, объединяющего различные подходы к контролю ресурсом АЭС. Представлены
результаты радиационного охрупчивания модельных сплавов, проанализированы данные
испытаний с использованием образцов-свидетелей, а также исследована надежность
корпусных и других типов сталей. Предложены перспективы развития разрушающих и
неразрушающих методов радиационного охрупчивания материалов. У рамках програми PLIM досліджено радіаційне окрнхчування і механізми
старіння конструкційних сталей та реакторів із метою оцінки, прогнозування
і моніторинга ресурсу відповідальних вузлів АЕС. Підсумовуються результати
проекту SAFELIFE, що об’єднує різні підходи щодо контролю
ресурсом АЕС. Представлено результати радіаційного окрихчування модельних
сплавів, проаналізовано дані випробувань із використанням зразків-
свідків, а також досліджується надійність корпусних та інших типів сталей.
Запропоновано перспективи розвитку руйнівних і неруйнівних методів радіаційного
окрихчення матеріалів.